Peran Revolusi Teknologi Informasi Dalam Mendorong Perubahan Sosial Dan Ekonomi Global - Ananda Rizki Akbar; Muhammad Irwan Padli Nasution (CV. SINAR HOWUHOWU, 2026)
The development of information technology (IT) has been a major catalyst in changing the social and economic landscape of the world. This revolution, which began with the era of computerization and continues with artificial intelligence (AI), has brought fundamental changes to work patterns, social structures, and the global economic order. This study aims to analyze how IT transformation affects social and economic dynamics, while examining emerging challenges such as the digital divide, data privacy, and the ethical implications of automation and algorithms. The results of the study show that although IT promotes efficiency and innovation, social sustainability can only be achieved through inclusive policies, digital literacy, and ethical technology governance.